Pengetahuan Lanjut Usia Tentang Covid-19 di Desa Simangulampe Kecamatan Baktiraja Kabupaten Humbang Hasundutan Tahun 2021 - Togi Marito Santa Monika Manullang (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Knowledge is the ability to receive, store, and use information, which is influenced by experience and skills. Covd-19 or often called 2019 coronavirus disease is a disease that infects the acute respiratory tract and is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Middle East Respiratory Syndrome (MERS-CoV). The purpose of the study was to determine the knowledge of the elderly about Covid-19 in Simangulampe Village, Baktiraja District, Humbang Hasundutan Regency in 2021. The research uses a qualitative method where data collection is done by interviewing 5 questions so as to be able to dig deeper into knowledge about Covid-19. The sampling technique used purposive sampling as many as 18 respondents. The data analysis technique used is thematic analysis. The results obtained: Covid-19 is an infectious virus and is an infectious disease that attacks the respiratory tract caused by the corona virus. The cause of Covid-19 is a corona virus that infects animals and spreads to humans. Common symptoms of being infected with Covid-19 include fever, shortness of breath, cough, runny nose, sore throat, loss of sense of smell, but for some patients there are no symptoms. The mode of transmission of Covid-19 is direct contact with patients, not complying with health protocols such as not wearing a mask, and through contaminated air. Prevention of Covid-19 can be done by avoiding crowds, carrying out health protocols such as washing hands, wearing masks, maintaining a diet, diligently exercising, not smoking and diligently exercising.